Peningkatan Pengetahuan Keluarga Penderita Tuberkulosis Tentang Perlunya Pendampingan Selama Pengobatan Dalam Meningkatkan Kepatuhan Di Puskesmas Pegajahan Kecamatan Serdang Bedagai - Nixson Manurung (Pusat Riset dan Inovasi Nasional, 2021)
Tuberculosis is a disease caused by Mycobacterium bacteria and until now it is still a disease with a high burden for the Indonesian people. The increasing burden of TB is caused by poverty, the failure of TB activities which has so far been caused by inadequate political commitment and funding, unavailability of services in the community causing reduced problem innovation and inappropriate diagnosis, reduced supply of medicines and reduced reporting of tuberculosis sufferers. lack of surveillance, lack of discourse on recording and reporting of cases, treatment management and the movement of people who are not reported. Compliance with TB patients in North Sumatra tends to decrease, namely in 2015 the level of compliance of TB patients for treatment was 88.20 percent and decreased to 79.68 percent in 2018. The method used was descriptive observational with 20 participants who were families of tuberculosis sufferers at the Pegajahan Health Center, Serdang Bedagai. The PkM team provided the material in question 1) The definition of tuberculosis, 2) The importance of the family providing assistance 3) How to take DOTS medication correctly, and 4) Patient compliance in taking medication. The results after the implementation of the activity 1) The majority of tuberculosis (TB) is good as many as 19 people, 2) The importance of the family to accompany the majority is good as many as 18 people, 3) How to take tuberculosis medicine the majority is good as many as 18 people, 4) The majority of patients' compliance with taking medication is good as many as 19 people. Increased knowledge and skills of participants because the community has a great desire to treat and prevent dengue fever in family members at home.